Does the diurnal pattern of enteric methane emissions from dairy cows change over time? - Bell, M.J.; Craigon, J.; Saunders, N.; Goodman, J.R.; Garnsworthy, P.C. (Cambridge University Press, 2018)
Diet manipulation and genetic selection are two important mitigation strategies for reducing enteric methane (CH4) emissions from ruminant livestock. The aim of this study was to assess whether the diurnal pattern of CH4 emissions from individual dairy cows changes over time when cows are fed on diets varying in forage composition. Emissions of CH4 from 36 cows were measured during milking in an automatic (robotic) milking station in three consecutive feeding periods, for a total of 84 days. In Periods 1 and 2, the 36 cows were fed a high-forage partial mixed ration (PMR) containing 75% forage, with either a high grass silage or high maize silage content. In Period 3, cows were fed a commercial PMR containing 69% forage. Cows were offered PMR ad libitum plus concentrates during milking and CH4 emitted by individual cows was sampled during 8662 milkings. A linear mixed model was used to assess differences among cows, feeding periods and time of day. Considerable variation was observed among cows in daily mean and diurnal patterns of CH4 emissions. On average, cows produced less CH4 when fed on the commercial PMR in feeding Period 3 than when the same cows were fed on high-forage diets in feeding Periods 1 and 2. The average diurnal pattern for CH4 emissions did not significantly change between feeding periods and as lactation progressed. Emissions of CH4 were positively associated with dry matter (DM) intake and forage DM intake. It is concluded that if the management of feed allocation remains constant then the diurnal pattern of CH4 emissions from dairy cows will not necessarily alter over time. A change in diet composition may bring about an increase or decrease in absolute emissions over a 24-h period without significantly changing the diurnal pattern unless management of feed allocation changes. These findings are important for CH4 monitoring techniques that involve taking measurements over short periods within a day rather than complete 24-h observations.